Kenya Economic Update, November 2020 : Navigating the Pandemic - World Bank (World Bank, Nairobi, 2020)
Kenya’s economy has been hit hard by COVID-19, severely affecting incomes and jobs. The economy has been exposed through the dampening effects on domestic activity of the containment measures and behavioral responses, and through trade and travel disruption (affecting key foreign currency earners such as tourism and cut flowers). Real Gross Domestic Product (GDP) contracted by 0.4 percent in H1 2020 year-on-year(y/y), compared to growth of 5.4 percent in H1 of 2019. This reflects a worse-than-anticipated Q2 GDP outturn, mainly due to a sharp reduction of services sector output, especially education. As a result, the economy is projected to contract by 1.0 percent in 2020 in the baseline scenario, and by 1.5 percent in a more adverse scenario. This revision essentially adopts the adverse scenario outlined in the April 2020 update, reflecting the more severe impact of the pandemic to date than had been initially anticipated, including on the measured output of the education sector following the closure of institutions in March. The special focus topic finds that the pandemic increased poverty by 4 percentage points (or an additional 2 million poor) through serious impacts on livelihoods, by sharp decreases in incomes and employment. The unemployment rate increased sharply,approximately doubling to 10.4 percent in the second quarter as measured by the KNBS Quarterly Labor Force Survey. Many wage workers who are still employed face reduced working hours, with average hours decreasing from 50 to 38 hours per week. Almost 1 in 3 household runbusinesses are not currently operating, and between February and June average revenue from household run businesses decreased by almost 50 percent. This has exacerbated food insecurity, and elevated pain and human suffering. In response to the crisis, the government has deployed both fiscal and monetary policies to support the healthcare system, protect the most vulnerable households, and support firms to help preserve jobs,incomes and the economy’s productive potential. Tax revenue dropped below target, due to the marked slowdown in economic activity, as well as tax relief as part of the government’s fiscal response package. At the same time, expenditures were raised to strengthen the capacity of the healthcare system to manage infections, protect the most vulnerable households, and support businesses.